2009
DOI: 10.1002/micr.20720
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative monitoring of lower limb free flaps with the Cook–Swartz implantable Doppler probe: A clinical trial

Abstract: A trend toward early detection and salvage of flaps with anastomotic insufficiency was seen with the use of the Cook-Swartz implantable Doppler probe. These findings suggest a possible benefit of this technique as a stand-alone or adjunctive tool in the clinical monitoring of free flaps, with further investigation warranted into the broader application of these devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 29 publications
2
48
0
1
Order By: Relevance
“…In this series of 592 flaps, we excluded demographic data because numerous reports in the literature show that smoking, age, BMI, history of cardiovascular disease, diabetes and previous irradiation of the recipient site have no significant effect on flap failure rates [24][25][26][27]. During this study, our experience with other flap monitoring techniques was limited and when used, they were of limited effectiveness.…”
Section: Discussionmentioning
confidence: 94%
“…In this series of 592 flaps, we excluded demographic data because numerous reports in the literature show that smoking, age, BMI, history of cardiovascular disease, diabetes and previous irradiation of the recipient site have no significant effect on flap failure rates [24][25][26][27]. During this study, our experience with other flap monitoring techniques was limited and when used, they were of limited effectiveness.…”
Section: Discussionmentioning
confidence: 94%
“…A tailored latissimus dorsi musculocutaneous flap is harvested with subsequent microsurgical anastomosis to the target vessel with preferential end-to-side anastomosis of the artery and end-to-end anastomosis of one or two veins. [18,29,30], die nicht-invasive kombinierte Laser-Doppler-Spektrophotometrie [16,36] oder auch die konfokale Lasermikroskopie [2]. Bezüglich der perioperativen Antikoagulation gibt es derzeit keine leitlinienbasierten Empfehlungen [20].…”
Section: Free Latissimus Dorsi Flap Transfer For Reconstruction Of Sounclassified
“…The commonest method of monitoring is carried out clinically and is based on subjective clinical observations. These tests are carried out on an island of skin or ‘skin paddle’—an area of skin considered to be indicative of the whole flap's arterial perfusion and venous drainage 12. Such tests may include the colour, capillary refill or blanching time, skin temperature, turgor and degree of bleeding in response to pin-prink and use of a handheld Doppler device 13…”
Section: Introductionmentioning
confidence: 99%
“…The Doppler provides monitoring for 5–10 days postoperatively and is removed by simple traction 18. A number of studies have shown that the use of this device increases success and salvage rates as it provides an earlier warning than the current method of clinical monitoring 12 21 22…”
Section: Introductionmentioning
confidence: 99%